Analisis Kualitas Aplikasi Simpel Pol Menggunakan Metode McCall - Maulidya Andini; Gita Fadila Fitriana (STMIK Budi Darma, 2022)
The Simpel Pol application is a health test service application for submitting a Driving License (SIM). The Purbalingga Police Clinic has implemented the use of the Simpel Pol application for the Purbalingga Regency area since April 2021. After searching in the Google Playstore review column, the Simple Pol application has several problems such as less accurate on hearing tests, applications that run slowly, and difficulty signing in. Based on these problems, this study aims to analyze the quality of the Simple Pol application using the McCall method. Product operation is used as the main perspective in this study with the metrics of completeness, consistency, traceability, error tolerance, accuracy, simplicity, execution efficiency, access control, operability, training, and communicativeness. The subject of this study is a driver's license applicant in the Purbalingga Regency who performs a medical test through the Simpel Pol application. The number of respondents was determined by the Slovin formula and data was collected using a questionnaire. The results of this study will determine the quality of the Simpel Pol application which is categorized as very good, good, good enough, not good, or very bad